The Role of Locus of Control, Financial Knowledge and Income on Financial Management Behavior : PLS-SEM Analysis - Zaidan Prayuda, Rafie; Purwanto, Agus (PROFESOR : Professional Education Studies and Operations Research, 2024)
The aim of this research is to analyze the relationship between Locus of Control and Financial Management behavior. Financial Knowledge on Financial Management behavior, Personal income on financial management behavior. Sample this research consisted of 654 respondents who were determined using the purposive sampling method. Data collection in this research used a questionnaire instrument distributed via Google Forms. The data analysis technique uses path analysis with the partial least squares structural equation modeling (PLS-SEM) method with data processing tools using Smart-PLS 3.0 software. Questionnaire is closely designed, except for the questions/statements concerning the respondent’s identity, which is a semi-opened questionnaire. Every closed questions/statement, five answer options is given in Likert scale, which consist of: strongly agree (SA) with 5 scores, agree (A) with 4 scores, Neutral (N) with 3 scores, disagree (DA) with 2 scores, and strongly disagree (SDA) with 1 score. The method in data processing is by using PLS and SmartPLS 3.0 software as the tool. The results of this research are that Locus of Control has a positive relationship with Financial Management behavior. Financial Knowledge has a positive relationship with Financial Management behavior, Personal income has a positive relationship with financial management behavior.